2018
DOI: 10.1371/journal.pone.0202411
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aphid parasitism on host plant fitness in an aphid-host relationship

Abstract: Aphids are serious agricultural insect pests which exploit the phloem sap of host plants and thus transmit pathogens to their hosts. However, the degree to which aphid parsitism affects the fitness of the host plants is not well understood. The aphid, Macrosiphoniella yomogicola, parasitizes the mugwort Artemisia montana in Japan. During summer most mugworts carry aphids, but most aphid colonies die out after the budding of A. montana inflorescences in late summer. A few aphid colonies survive to late autumn, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…From late June to early August, most of the mugwort shoots are inhabited by the mixed morph aphid colonies. After inflorescences of the host shoot have emerged, aphid colonies rapidly decrease [10]. When an aphid colony survives until mid-October when sexuparae of M. yomogicola emerge, inhabited shoots rarely produce inflorescences.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…From late June to early August, most of the mugwort shoots are inhabited by the mixed morph aphid colonies. After inflorescences of the host shoot have emerged, aphid colonies rapidly decrease [10]. When an aphid colony survives until mid-October when sexuparae of M. yomogicola emerge, inhabited shoots rarely produce inflorescences.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the attending ants prefer the green morph under both experimental and field conditions [10], likely owing to the highquality honeydew excreted by the green morph. If this observation is correct, although the ants can discriminate between the morphs since they manipulate the green morph only, why is the red morph maintained in aphid colonies by the ants?…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this research, we did not investigate the effect of aphids on the growth of C. odorata but presumably has a similar effect with C. connexa. Research by Watanabe et al (2018) found that the parasitism of aphid, Macrosiphoniella yomogicola, in the mugwort (Artemisia montana) did not affect the host plant growth, but significantly decreased the number of inflorescences.…”
Section: Effect Of Land-use Type and Altitude On C Odorata C Connementioning
confidence: 99%